2020 International Conference on UK-China Emerging Technologies (UCET) 2020
DOI: 10.1109/ucet51115.2020.9205464
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Care: Using Deep Learning for Multi-Domain Activity Classification

Abstract: Nowadays, health monitoring issues are increasing as the worldwide population is aging. In this paper, the radar modality is used to classify with radar signature automatically. The classic approach is to extract features from micro-Doppler signatures for classification. This data representation domain has its limitations for activities presenting similar accelerations like a frontal fall and picking up an object from the floor that lead to wrongly labeled activities. In this work, we propose to combine multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In this work, spectrograms are used to capture the various velocity patterns of different body parts in human movements. However, recent works [17], [82], [83] have shown that combining multidomain information for HAR can also be advantageous, e.g., combining the RD, DT, CVD, and RT information.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, spectrograms are used to capture the various velocity patterns of different body parts in human movements. However, recent works [17], [82], [83] have shown that combining multidomain information for HAR can also be advantageous, e.g., combining the RD, DT, CVD, and RT information.…”
Section: Discussionmentioning
confidence: 99%
“…[46] proposed CNN based angel assistance system (AAS) to improve the fall detection accuracy performance of the AAS for the elderly by minimizing the false positive alerts. The CNN model achieved 98% accuracy with more or less of 17% reduction in the false positive alerts compared to the conventional AAS [51] proposed CNN for multi-domain activity classification in elderly healthcare. The CNN extracts pattern features and classifies based on six different possible activities.…”
Section: A Application Of Convolutional Neural Network For Developing...mentioning
confidence: 95%
“…Up to now, the most common methods of human activity detection are visionbased detection like using cameras and sensor-based detection such as using wearable sensors, radar and smartphone sensors [3,4]. Among all the methods, radar technology outperforms the other for the following aspects [5][6][7][8]. Environmental insensitivity: radar detection is not influenced by harsh light; Contactless Sensing: users do not need to wear or connect with any devices, which provides a high capability of comfort and convenience; Privacy Protection: radar technology collects human activity data without showing their actual images, ensuring the privacy of individuals.…”
Section: Contextmentioning
confidence: 99%
“…As machine learning developed, many researchers began to directly consider the grayscale of RGB images of spectrograms as features. Then, convolutional neural networks derived from vision-based classification were applied to those images for classification [3][4][5][6][7]10,22]. Compared with the conventional hand-crafted feature extraction approaches, the use of deep learning technology can increase the accuracy in classification.…”
Section: Micro-doppler Maps (Spectrograms)mentioning
confidence: 99%